Mechanisms of carbon dioxide acquisition and CO2 sensing in marine diatoms: a gateway to carbon metabolism. (5th September 2017) - Matsuda, Yusuke; Hopkinson, Brian M.; Nakajima, Kensuke; Dupont, Christopher L.; Tsuji, Yoshinori
Abstract : Diatoms are one of the most successful marine eukaryotic algal groups, responsible for up to 20% of the annual global CO2 fixation. The evolution of a CO2 -concentrating mechanism (CCM) allowed diatoms to overcome a number of serious constraints on photosynthesis in the marine environment, particularly low [CO2 ]aq in seawater relative to concentrations required by the CO2 fixing enzyme, ribulose-1, 5-bisphosphate carboxylase/oxygenase (RubisCO), which is partly due to the slow diffusion rate of CO2 in water and a limited CO2 formation rate from in seawater. Diatoms use two alternative strategies to take up dissolved inorganic carbon (DIC) from the environment: one primarily relies on the direct uptake of through plasma-membrane type solute carrier (SLC) 4 family transporters and the other is more reliant on passive diffusion of CO2 formed by an external carbonic anhydrase (CA). Bicarbonate taken up into the cytoplasm is most likely then actively transported into the chloroplast stroma by SLC4-type transporters on the chloroplast membrane system. Bicarbonate in the stroma is converted into CO2 only in close proximity to RubisCO preventing unnecessary CO2 leakage. CAs play significant roles in mobilizing DIC as it is progressively moved towards the site of fixation. However, the evolutionary types and subcellular locations of CAs are not conserved between different diatoms, strongly suggesting that this DIC mobilization strategy likely evolved multiple times with different origins. By contrast, the recent discovery of the thylakoid luminal θ-CA indicates that the strategy to supply CO2 to RubisCO in the pyrenoid may be very similar to that of green algae, and strongly suggests convergent coevolution in CCM function of the thylakoid lumen not only among diatoms but among eukaryotic algae in general. In this review, both experimental and corresponding theoretical models of the diatom CCMs are discussed. This article is part of the themed issue 'The peculiar carbon metabolism in diatoms'.